Intraoperative cystoscopy in major gynaecological surgeries: necessary skill for a gynecologist - Mishra, Vineet V.; Solanki, Smit B.; Aggarwal, Rohina; Choudhary, Sumesh; Shah, Kunur; Anusha, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: The goal of this study is to find out: how important it is to utilize intraoperative cystoscopy liberally in normal gynaecological procedures to detect urinary tract injuries, how long it takes to do intraoperative cystoscopy and what problems are linked with cystoscopy. Materials: The study is from the year 2016 to 2022 involving around 1221 patients. In a tertiary care facility, retrospective observational research was conducted. The study comprised patients receiving all gynaecological and urogynaecological operations. Malignancy was ruled out. Following gynaecological surgery, a 20-F-30-degree telescope was used to perform a cystourethroscopy. To record case information, a study proforma was created. Results: Intraoperative cystoscopy detected four bladder injuries during anti-incontinence surgery (TVT) and hysterectomy. After a thorough laparoscopic hysterectomy with normal cystoscopy, one patient returned one month later with right ureteric injury. A urinary tract infection struck fifteen people shortly after surgery. After surgery, one patient suffered flank pain and a fever for 48 hours. There was no sign of urinary tract injury on a CT-IVP scan. She was handled with care. Conclusions: For early diagnosis of urinary tract injuries, gynaecologists should have a low threshold for performing intraoperative cystoscopy during gynaecological procedures. Early detection and treatment of urinary tract injuries reduces the patient's morbidity, with a successful repair outcome at the time of detection. Performing an intraoperative cystoscopy during gynaecological procedures allows for this.